EVALUACIÓN DE LA ACTIVIDAD ANTIMICROBIANA DE LOS ACEITES ESENCIALES DE JENGIBRE (Zingiber officinale Roscoe) Y NARANJA (Citrus x sinensis) EN UNA SALCHICHA DE POLLO - Muentes Bazurto, Anderson Daniel (2023)
The objective of the project is to determine the preservative effect of essential oils of ginger (Zingiber officinale Roscoe) and orange (Citrus x sinensis) as a preservative in chicken sausages, The aim of this study was to establish the optimum concentration of these oils to be used in the preparation of chicken sausages, since a meat product is prone to deterioration either by oxidation or by the incidence or presence of microorganisms, which is why the meat industry uses nitrites or antioxidants for preservation. This was studied by means of a multifactorial design A x B + 1 with 3 replications where the influence of the two types of essential oils (Ginger and Orange) at different concentrations (300 ppm and 500 ppm) on the preservation of chicken sausage was evaluated and compared with a control (sausages with synthetic additives - sodium nitrite). To establish the effects between the levels of the treatments, Tukey's significance test was applied (p<0.05), the result of the data obtained was analyzed by means of the statistical package "STATGRAPHICS" and "MINITAB". Regarding the types of essential oils and concentrations, it was possible to establish through validation of the quality of the product in terms of microbiological analysis (Staphylococcus Aureus, Escherichia Coli and Salmonella) and physicochemical analysis (acidity and pH) that the optimum concentration based on the results obtained is 500 ppm.